Historiography of the Morava Architecture: Controversial Points of the Study - Mal’tseva, Svetlana V. (Actual Problems of Theory and History of Art, 2018)
Based on the historiographic material the article is addressed to the main problems in the study of the Serbian Morava architecture. In the 19th century the first critical research of the Serbian architecture placed it between the East and the West, formed certain approaches, and indicated some of the key issues influencing the study of the monuments of the Morava region. In the beginning of the 20th century the definition of the Morava architecture was given by G. Millet who puts it in the ending of the proposed by him periodization of the Serbian medieval architecture seen as the array of separate ‘schools’ divided chronologically and geographically. G. Millet identifies the monuments of the ‘Morava school’ relying on the typological and stylistic uniformity, as well as territorial separation. Their main typological feature is the triсonch plan, which exists in two basic versions: a single-nave church or a four-pillared cross-dome church with separately standing pillars. Millet’s view on the specifics and chronology of the ‘Morava School’ up to now continues to exist as the base view on the history of Serbian architecture. However, further findings and the studying of the monuments accumulated a number of issues which destroyed the harmony the original concept. The subsequent study of the Morava architecture once again raised the questions of the chronology of the monuments, their relationship to Byzantine and earlier Serbian traditions, as well as the extent and the nature of Western influences. Even the issue of the origin of such a bright typological feature as the triconch plan is still controversial. At the moment, it became clear that as a definition of the last period of the Serbian medieval architecture, the term ‘Morava school’ is hardly unambiguous and applicable, because there is no clear stylistic unity among the monuments of that era and no information neither about the terms of their construction, nor the craftsmen involved in it. In our view, the topics of the content, specifics, and mechanisms of the formation and evolution of the Serbian Morava architecture as an integrated regional phenomenon are to be put into foreground of modern research.